Dice and pulsars - Kontorovich, V.M. (Вопросы атомной науки и техники, 2007)
The pulse sequence is interpreted as a realization of a random electron discharge process in a vacuum gap over the polar cap (PC) —the open magnetic force line region on the neutron star surface. This point of view is illustrated by an example based on the dice. The generators of the random numbers are a cube and a coin. Throwing of dice and coin tossing determine the discharge places on the “light” and “dark” sides of PC, and correspondingly — the “shape” of the individual pulses and their statistical properties The physical mechanism giving such discharge scheme is shortly discussed. It may be a charge drained down from a sharp top of surface waves in a parallel electric field on the liquid PC surface of a neutron star.